Something more about Peruvian arielismo: Response to an article by Ricardo Portocarrero - Gonzales Alvarado, Osmar (1998)
In number 50 of the magazine Allpanchis Phuturinqa appeared an intelligent article by Ricardo Portocarrero entitled "Veto or failure? Notes on the Peruvian intelligentsia during the Aristocratic Republic" in which, taking as a starting point the criticism he makes of a book of mine Dedicated to the Peruvian arielist intellectuals, it expresses their ideas regarding that great issue that intellectuals constitute and refers to our country. I cannot fail to thank you for your interest in my book, as well as acknowledging that there are many topics that need to be investigated in greater detail.